The prognostic value of sarcopenia in oesophageal cancer: A systematic review and meta‐analysis. Issue 1 (22nd November 2022) - Fang, Pinhao; Zhou, Jianfeng; Xiao, Xin; Yang, Yushang; Luan, Siyuan; Liang, Zhiwen; Li, Xiaokun; Zhang, Hanlu; Shang, Qixin; Zeng, Xiaoxi; Yuan, Yong
Abstract: The loss of skeletal muscle mass and function is defined as sarcopenia, which might develop in elderly patients with cancers. It has been indicated as a potential negative factor in the survival of patients with malignant tumours. The aim of this systematic review and meta‐analysis was to evaluate the associations between sarcopenia and survival outcomes or postoperative complications in patients with oesophageal cancer (EC). Web of Science, Embase, Medline, and Cochrane Library databases were searched until 10 May 2022, using keywords: sarcopenia, oesophageal cancer, and prognosis. Studies investigating the prognostic value of sarcopenia on EC survival were included. Forest plots and summary effect models were used to show the result of this meta‐analysis. The quality of included studies was evaluated with the Newcastle‐Ottawa Scale (NOS). A total of 1436 studies were identified from the initial search of four databases, and 41 studies were included for the final quantitative analysis. This meta‐analysis revealed a significant association between sarcopenia and overall survival (OS) [hazard ratios (HR):1.68, 95% confidence interval (CI):1.54–1.83, P  = 0.004, I 2  = 41.7%] or disease‐free survival (DFS) 1.97 (HR: 1.97, 95% CI: 1.44–2.69, P  = 0.007, I 2  = 61.9%) of EC patients. Subgroup analysis showed that sarcopenia remained a consistent negative predictor of survival when stratified by different treatment methods, populations, or sarcopenia measurements. Sarcopenia was also a risk factor for postoperative complications with a pooled odds ratio of 1.47 (95% CI: 1.21–1.77, P  = 0.094, I 2  = 32.7%). The NOS scores of all included studies were ≥6, and the quality of the evidence was relatively high. The results from the study suggested that sarcopenia was significantly associated with both survival outcomes and postoperative complications in EC patients. Sarcopenia should be appropriately diagnosed and treated for improving short‐term and long‐term outcomes of patients with EC.